The late trading and market-timing scandal of mutual funds - Shichor, David (Crime, law and social change, 2012)
The first decade of the 21st century witnessed several major financial scandals. One of the less studied of these by criminologists is the late trading and market-timing scandal that involved several major mutual funds, hedge funds, money managers and brokerage firms. Until this scandal was revealed in 2003, the mutual fund industry was considered a "clean" industry in which people with modest means could make long term investments with relatively low risk. The late trading/market-timing scandal changed this situation by harming these long-term investors.